2023
DOI: 10.3390/polym15061550
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterisation of an Exopolysaccharide by Bacillus amyloliquefaciens: Biotechnological Applications

Abstract: The Bacillus amyloliquefaciens RT7 strain was isolated from an extreme acidic environment and identified. The biodegradation capabilities of the strain using different carbon sources (glucose, oleic acid, Tween 80, PEG 200, and the combination of glucose–Tween 80) were evaluated via an indirect impedance technique. The glucose–Tween 80 combination was further studied using nuclear magnetic resonance (NMR). The exopolysaccharide (EPSRT7) that had been produced with the strain when biodegrading glucose–Tween 80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…The peak at 1600 cm −1 and 1401 cm −1 was attributed to the ionic carboxyl group (COO-) and C-H bond vibration, respectively [75]. According to a previous study, the absorption at 1246 cm −1 could be attributed to the pyranose ring [37]. Absorption peaks in the 1160 cm −1 region indicated C-O-C stretching vibration and the peak at 1018 cm −1 was due to C-O-H stretching vibration [76].…”
Section: Characterization Of the Exopolysaccharidesmentioning
confidence: 87%
See 4 more Smart Citations
“…The peak at 1600 cm −1 and 1401 cm −1 was attributed to the ionic carboxyl group (COO-) and C-H bond vibration, respectively [75]. According to a previous study, the absorption at 1246 cm −1 could be attributed to the pyranose ring [37]. Absorption peaks in the 1160 cm −1 region indicated C-O-C stretching vibration and the peak at 1018 cm −1 was due to C-O-H stretching vibration [76].…”
Section: Characterization Of the Exopolysaccharidesmentioning
confidence: 87%
“…However, the EPS obtained from 0.6 M Choline NTF2, presented 47% higher activity than the other EPSs for vegetable oils, and even higher in hydrocarbons, with a 60% increase in emulsifying activity for 0.6 M Choline NTF2. This indicated that the morphology of the EPS had a decisive role in this activity [37]. The results indicated that at a concentration of 1 mg, the EPS only presented a better emulsifying (p < 0.05) activity for diesel ((E24) 60%) compared with commercial emulsifiers (Triton X-100 ((E24) 50%), Tween 20 ((E24) 50%) and SDS ((E24) 37.5%)).…”
Section: Emulsifying Studymentioning
confidence: 94%
See 3 more Smart Citations